The effectiveness of Alexander's theory in the practice of middle school mathematics teachers for dialogic teaching - Alzubaidi, Ibrahim Abdah Ali (Edelweiss Applied Science and Technology, 2025)
The current study aimed to identify the effectiveness of Alexander's theory in the practice of middle school mathematics teachers for dialogic teaching. To achieve the study's objectives, the researcher prepared a tool consisting of three axes: (Principles of Dialogic Teaching, Classifications of Dialogic Teaching, Indicators of Dialogic Teaching). The questionnaire comprised 46 items, and the sample of the study included 65 male and female teachers from the middle school level in the Al-Qunfudhah Governorate, selected randomly during the second semester (2025 AD/1446 AH). The study revealed the following results: the arithmetic averages for the first axis on the principles of dialogic teaching were rated as 'medium,' the second axis on 'Classifications of Dialogic Teaching' was rated as 'high,' and the third axis on 'Indicators of Dialogic Teaching' was rated as 'medium.' Moreover, there were statistically significant differences based on the gender variable in favor of males, and statistically significant differences based on the educational qualification variable in favor of those holding a master's degree and doctorate. There were also statistically significant differences concerning experience, favoring those with 5 to 10 years of experience. The study recommended providing an organized and safe classroom environment free from all distractions and adopting classroom designs that consider interaction with sufficient time for dialogue during lessons.